2021
DOI: 10.1016/j.redox.2021.101971
|View full text |Cite
|
Sign up to set email alerts
|

HO-1-mediated ferroptosis as a target for protection against retinal pigment epithelium degeneration

Abstract: Oxidative stress-mediated retinal pigment epithelium (RPE) degeneration plays a vital role in retinal degeneration with irreversible visual impairment, most notably in age-related macular degeneration (AMD), but a key pathogenic factor and the targeted medical control remain controversial and unclear. In this work, by sophisticated high-throughput sequencing and biochemistry investigations, the major pathologic processes during RPE degeneration in the sodium iodate-induced oxidative stress model has been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(110 citation statements)
references
References 53 publications
(64 reference statements)
2
86
0
Order By: Relevance
“…Hiramitsu et al (1976) reported photoreceptor degeneration induced by IVT injections of linoleic acid hydroperoxide in rabbits. Ferroptosis, an irondependent programmed cell death pathway, is accompanied by lipid peroxide accumulation (Yang & Stockwell, 2016) and occurs in the sodium iodate retinal degeneration model (Tang et al, 2021). Taken together, iron may induce retinal degeneration via peroxidation of polyunsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Hiramitsu et al (1976) reported photoreceptor degeneration induced by IVT injections of linoleic acid hydroperoxide in rabbits. Ferroptosis, an irondependent programmed cell death pathway, is accompanied by lipid peroxide accumulation (Yang & Stockwell, 2016) and occurs in the sodium iodate retinal degeneration model (Tang et al, 2021). Taken together, iron may induce retinal degeneration via peroxidation of polyunsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…They first observed that sodium iodate increased intracellular labile iron, while decreasing intracellular glutathione and cysteine. Using deferoxamine or ferrostatin-1, two ferroptosis inhibitors, ARPE-19 cell death was prevented from sodium iodate exposure [110,111]. These studies together support the relatively strong association between RP and ferroptosis (Figure 1).…”
Section: Ferroptosis Regulation In Rpmentioning
confidence: 53%
“…However, data on other ferroptosis regulators, such as ferrostatin-1 and liproxstatin-1 on RP models, are still lacking. Recently, two new studies found that ferroptosis is involved in sodium iodate-induced ARPE-19 cell death, suggesting that ferroptosis is involved in retinal degeneration, which supports the association with RP [110,111]. They first observed that sodium iodate increased intracellular labile iron, while decreasing intracellular glutathione and cysteine.…”
Section: Ferroptosis Regulation In Rpmentioning
confidence: 72%
“…HMOX1 is an inducible enzyme that catalyzes heme conversion into biliverdin, carbon monoxide, and free ferrous during oxidative stress. From a mechanistic perspective, HMOX1 can also release carbon monoxide and free iron ions, thereby aggravating oxidative stress [21]. The upregulation of HMOX1 is evident in many different human malignancies, wherein it plays an important role in regulating the stability of the tumor microenvironment in a manner that promotes tumor cell proliferation, angiogenesis, and metastasis [21].…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanistic perspective, HMOX1 can also release carbon monoxide and free iron ions, thereby aggravating oxidative stress [21]. The upregulation of HMOX1 is evident in many different human malignancies, wherein it plays an important role in regulating the stability of the tumor microenvironment in a manner that promotes tumor cell proliferation, angiogenesis, and metastasis [21]. However, HMOX1 can also promote ferroptosis in cancer cells in therapeutic contexts [22].…”
Section: Discussionmentioning
confidence: 99%